2019
DOI: 10.5296/jas.v7i3.15271
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Apple Plants to Drought Stress

Abstract: In order to screen apple rootstocks for drought tolerance, two different drought levels moderate and severe stress, and a control were applied to apple cultivar Red Chief grafted onto M9 and MM106 rootstocks. Apple plants were subjected to drought stress by withholding water for 15 and 19 days in the greenhouse conditions, while the control treatment was continued watering. Data were recorded 15 (moderate drought stress) and 19 days (severe drought stress) after application of drought stress. At the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…Salinity damages of salt stress have been previously explained in temperate fruit trees. Decrease in leaf chlorophyll and water status and increment in cell membrane permeability were reported in apple (Yin et al, 2010;Aras and Eşitken, 2019a) and sweet cherry (Aras and Eşitken, 2019b). García-Legaz et al (2008) stated that salinity depressed loquat plant growth that could be attributed to decreases in CO 2 assimilation, photosynthesis and leaf gas exchange.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Salinity damages of salt stress have been previously explained in temperate fruit trees. Decrease in leaf chlorophyll and water status and increment in cell membrane permeability were reported in apple (Yin et al, 2010;Aras and Eşitken, 2019a) and sweet cherry (Aras and Eşitken, 2019b). García-Legaz et al (2008) stated that salinity depressed loquat plant growth that could be attributed to decreases in CO 2 assimilation, photosynthesis and leaf gas exchange.…”
Section: Introductionmentioning
confidence: 96%
“…Salinity is a common stress in plants caused by excessive fertilization, drought and poor drainage in soils (Aras and Eşitken, 2018;Pehlivan and Güler, 2019). Many fruit trees including sweet cherry plants are known to sensitive to salt stress (Aras et al, 2019;Aras and Eşitken, 2019a). Salinity damages of salt stress have been previously explained in temperate fruit trees.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf stomata and pigments take important roles in photosynthesis (Aras & Eşitken, 2019b;Candar et al, 2020). In the study, SNP and ASA elevated stomatal conductance by increasing stomatal density and area.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that bacterial applications had a more positive effect on chlorophyll content which is one of the most important factors determining photosynthesis capacity and these results were in agreement with many similar studies (Aydın et al, 2012;Güllüce et al, 2012;Heidari et al, 2011). SPAD value reflects chlorophyll content decreases under stress conditions (Aras and Eşitken, 2019b;Aras and Keles, 2019). Akay and Kararaslan (2012) reported that mycorrhiza applications, especially in poor soils, contribute significantly to chlorophyll content in plants.…”
Section: Chlorophyll and Anthocyanin Contentmentioning
confidence: 99%